Strategi Pemasaran Produk Gadai dalam Menarik Minat Nasabah di PT. Pegadaian UPS Sibuhuan - Sarmnia Hsb; Reni Ria Armayani Hasibuan (Universitas Muhammadiyah Surabaya, 2023)
The marketing strategy is basically a comprehensive, integrated and unified plan in the field of marketing, which provides guidance on the activities carried out in order to achieve the marketing objectives of a company. Customer interest in using Sharia Pawn products at Sibuhuan Sharia Pawnshops continues to increase. However, the increase in the number of customers has not been able to achieve the goals or the number of target customers that have been determined each year. This is due to the increasing number of competing companies or other financial institutions that offer pawn products. The formulation of the problem from this research is: what is the marketing strategy for pawn products carried out by the Sibuhuan Islamic Pawnshop (UPS) in attracting customer interest. This study aims to find out how the pawn product marketing strategy implemented by Sibuhuan Islamic Pawnshops (UPS) in attracting customer interest. This research is a type of qualitative research that is descriptive. Sources of data used in this study are primary data and secondary data. Data collection techniques include observation methods, interview methods, and documentation methods. There are three steps in the data analysis procedure, namely data reduction, data review and verification or conclusion. Then to test the validity of the data using triangulation techniques consisting of data source triangulation, technical triangulation and time triangulation. Pawn Sharia, namely by determining marketing planning (marketing mix) with four stages, namely determining consumer needs and wants, choosing target markets, placing marketing strategies in competition, and choosing marketing strategies. In choosing a marketing strategy, Pegadaian Syariah (UPS) Sibuhuan applies a marketing strategy, namely a marketing mix with 7P, including product strategy (Product), price strategy (Price), location strategy (Place), promotion strategy (Promotion), people strategy (People ), process strategy (Process), and physical environment strategy (Physical Evidence)